2002
DOI: 10.1590/s1415-47572002000300016
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection and family X location interaction in the common (dry) bean plant

Abstract: Ab stractNat u ral se lec tion takes place while ad vanc ing gen er a tions of segregant pop u la tions of s elf pol li nat ing spe cies by the pop u la tion (bulk) method. There is ev i dence that it main tains the in di vid u als with greate r grain yield. The ques tion arises whether nat u ral se lec tion pre serves the in di vid u als which are more adapted only to the en vi ron ment where the gen er a tion ad vance oc curred, that is, if it con trib utes to in creas ing the ge no type x en vi ron ment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
5
0
3
Order By: Relevance
“…This evidenced that the population performance did not coincide in the evaluation of the 20 distinct environments. This result agrees with those of Corte et al (2001) and Pirola et al (2002), in experiments conducted with common bean in different environments.…”
Section: Resultssupporting
confidence: 94%
“…This evidenced that the population performance did not coincide in the evaluation of the 20 distinct environments. This result agrees with those of Corte et al (2001) and Pirola et al (2002), in experiments conducted with common bean in different environments.…”
Section: Resultssupporting
confidence: 94%
“…Only five families of the 30 best (16.67%) were derived from the F 2 generation. It has also been reported that the action of natural selection con- Silva et al 577 tributed to preserve the best-adapted individuals (higher yielding) in crops such as in Triticum aestivum L (Gregan and Busch, 1978) Phaseolus lunatus L. (Tucker and Harding, 1974) and Phaseolus vulgaris L. (Pirola et al, 2002). All these results pointed towards the efficiency of the bulk method.…”
Section: Resultsmentioning
confidence: 91%
“…Para a obtenção de uma nova linhagem, são feitas avaliações por várias gerações. Nessa condição, espera-se que a seleção natural atue e que possam ser identificadas as mais adaptadas àquele ambiente particular (Gonçalves et al, 2001;Pirola et al, 2002;Silva et al, 2004). Assim, esperava-se que as linhagens oriundas de um local tivessem maior adaptabilidade e estabilidade no referido local.…”
Section: Resultsunclassified